BRCA mutation‐negative women from hereditary breast and ovarian cancer families: a qualitative study of the BRCA‐negative experience - Bakos, Alexis D. (Blackwell Publishing Ltd, 2008)
Background  When women from families with a known BRCA1 or BRCA2 mutation test negative for the family mutation, it is assumed that they will transition their personal cancer risk perception from high to average risk. However, there are scant data regarding the experience of mutation‐negative women after genetic testing disclosure, particularly related to the shift of risk perception from assumed mutation‐positive to actual mutation‐negative. This study was designed to explore cancer risk perception and the experience of being a mutation‐negative woman within a known BRCA1/2 mutation‐positive family. Methods  We employed a qualitative descriptive design and convened a sample of 13 women who contributed in‐depth, semi‐structured telephone interviews (audio‐recorded and transcribed verbatim) and performed qualitative content analysis with NVivo 2.0 software. Results  Six major content areas emerged from interview data: (i) rationale for initial involvement in the breast imaging study, (ii) rationale for continued participation, (iii) experience of living in a multiple‐case family, (iv) risk perception: the personal meaning of mutation‐negative status, (v) opinions regarding cancer aetiology and (vi) communication patterns between mutation‐negative and mutation‐positive family members. Conclusions  Living in a hereditary breast and ovarian cancer family is a complex experience that affects cognitive, emotional and social functioning. Our findings indicate that mutation‐negative women may have unmet psychosocial needs that must be addressed by health‐care professionals, particularly in the primary‐care setting following genetic disclosure of a potentially reassuring result regarding their lack of the very high cancer risks associated with BRCA1/2 mutations.